The development of creative cognition across adolescence: distinct trajectories for insight and divergent thinking. Issue 1 (8th October 2012) - Kleibeuker, Sietske W.; De Dreu, Carsten K.W.; Crone, Eveline A.
Abstract: We examined developmental trajectories of creative cognition across adolescence. Participants (N = 98), divided into four age groups (12/13 yrs, 15/16 yrs, 18/19 yrs, and 25–30 yrs), were subjected to a battery of tasks gauging creative insight (visual; verbal) and divergent thinking (verbal; visuo‐spatial). The two older age groups outperformed the two younger age groups on insight tasks. The 25–30‐year‐olds outperformed the two youngest age groups on the originality measure of verbal divergent thinking. No age‐group differences were observed for verbal divergent thinking fluency and flexibility . On divergent thinking in the visuo‐spatial domain, however, only 15/16‐year‐olds outperformed 12/13‐year‐olds; a model with peak performance for 15/16‐years‐old showed the best fit. The results for the different creativity processes are discussed in relation to cognitive and related neurobiological models. We conclude that mid‐adolescence is a period of not only immaturities but also of creative potentials in the visuo‐spatial domain, possibly related to developing control functions and explorative behavior. Abstract : We examined developmental trajectories of creative cognition across adolescence. Participants ( N = 98), divided into four age groups (12/13 yrs, 15/16 yrs, 18/19 yrs, and 25–30 yrs), were subjected to a battery of tasks gauging creative insight (visual;verbal) and divergent thinking (verbal; visuo‐spatial). The two older age groups outperformed the two younger age groups on insight tasks.